2017
DOI: 10.1007/s00261-017-1072-0
|View full text |Cite
|
Sign up to set email alerts
|

CT-based radiomics signature: a potential biomarker for preoperative prediction of early recurrence in hepatocellular carcinoma

Abstract: The radiomics signature was a significant predictor for early recurrence in HCC. Incorporating radiomics signature into conventional clinical factors performed better for preoperative estimation of early recurrence than with clinical variables alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
142
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(155 citation statements)
references
References 41 publications
11
142
2
Order By: Relevance
“…Previous reports have indicated that radiomics features could potentially be used as predictive or prognostic biomarkers (19)(20)(21). Although a radiomics signature based on CT textural features has been reported as a biomarker for the preoperative prediction of early recurrence in patients with HCC (22), to the best of our knowledge, no study to date has proposed that presence of MVI can be accurately predicted based on a radiomics signature.…”
mentioning
confidence: 93%
“…Previous reports have indicated that radiomics features could potentially be used as predictive or prognostic biomarkers (19)(20)(21). Although a radiomics signature based on CT textural features has been reported as a biomarker for the preoperative prediction of early recurrence in patients with HCC (22), to the best of our knowledge, no study to date has proposed that presence of MVI can be accurately predicted based on a radiomics signature.…”
mentioning
confidence: 93%
“…Radiomic biomarkers have been shown to be associated with several clinical endpoints, including survival (11,1416), nodule malignancy (17,18), pathological response (19,20), recurrence and distant metastasis (2123), as well as tumor gene expression patterns (11,14,21). A natural extension of this observation is that tumor phenotype should be linked to the tumor genotype.…”
Section: Introductionmentioning
confidence: 99%
“…Objective and quantitative imaging descriptors can improve the accuracy in diagnosis, evaluation of prognosis, and prediction of therapeutic response . According to previous studies, radiomic mineable quantitative data could serve as predictive or prognostic biomarkers . In the field of oncology, especially in lung cancer, radiomics is mostly used to facilitate the improvement diagnostic accuracy as well as making treatment decisions .…”
mentioning
confidence: 99%
“…10 According to previous studies, radiomic mineable quantitative data could serve as predictive or prognostic biomarkers. [13][14][15][16] In the field of oncology, especially in lung cancer, radiomics is mostly used to facilitate the improvement diagnostic accuracy as well as making treatment decisions. [16][17][18][19] Therefore, the objective of our study was to build and evaluate an MR-based radiomics nomogram that incorporates a radiomics signature and clinical parameters for preoperatively predicting the LVSI of cervical cancer.…”
mentioning
confidence: 99%